Identifikasi Morfologi dan Profil Fitokimia Buah Srikaya (Annona squamosa L.) Lokal Sumenep sebagai Kandidat Sumber Bahan Alam Fungsional - Hairul Anwar; Arifah Husna; Ahmad Syaiful Umam (Lembaga Pengembangan Kinerja Dosen, 2025)
Sugar apple (Annona squamosa L.) is one of the local fruit commodities with high potential as a source of functional natural ingredients. This study aims to identify the morphological characteristics and profile the phytochemical content of local Sumenep sugar apple fruit as a basis for the development of its bioactivity. Morphological observations were carried out in the Sumenep area, including fruit shape, size, stem circumference, leaf characteristics, and flower parts. Phytochemical analysis was conducted using qualitative tests for tannins and saponins, while tests for flavonoids and alkaloids are planned for the next stage. Observation results showed that local Sumenep sugar apple fruits have morphological variations in the form of ovoid, round, and oblong shapes, influenced by genetic factors and environmental conditions. Phytochemical tests showed the presence of tannins, indicated by a color change to dark green when using FeCl₃ reagent, as well as the presence of saponins, demonstrated by the formation of stable foam during the shaking test. These findings reinforce the potential of local Sumenep soursop fruit as a candidate source of functional natural compounds, particularly in relation to antioxidant, antimicrobial activities, and other pharmacological benefits. Further studies are needed to analyze other phytochemical contents and evaluate bioactive activities more comprehensively.